Bioconversion of pumpkin by-products in novel supplements supporting Lactobacillus casei - Genevois, Carolina Elizabeth (2019)
The aim of the work was to bio-convert pumpkin by-products in novel supplements supporting probiotics. The physicochemical and functional characterizations as well as the shelf life of the new product were analysed. Lower alcohol insoluble residue (AIR), 47 g/100 g, and higher protein, 12.2 g/100 g, were observed in the pumpkin powder supporting L. casei as the result of the probiotic growth. Water and oil holding capacities (23  g/g and 4.55  g/g, respectively) were not modified substantially due to probiotic presence. High non cellulosic carbohydrates content, ≈60 g/100 g AIR, as well as porous microstructure, helps to explain the remarkable hydration properties. The shelf life was determined by a L. casei count >106 CFU g−1 after the in vitro gastrointestinal digestion resulting 28 days at 22 °C. The supplement was tested in a commercial hot drink showing an increase in the probiotic survival of almost 4 log cycles respect to the free cells after 90 min at 63 °C. It could represent a relevant advantage for probiotic supplementation in hot preparations. Therefore the process shows potentiality for adding value to pumpkin by-products. In addition, it was successfully scaled up in one order of magnitude.